PENGARUH SENAM OTAK (BRAIN GYM) TERHADAP TINGKAT KONSENTRASI PADA SISWA DI SDN 01 BEDALISODO KECAMATAN WAGIR KABUPATEN MALANG - Wistiana; Rahayu Hastutiningtyas, Wahidyanti; Maemunah, Neni (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
The level of concentration in elementary school students is still a challenge for educators, where students' concentration is currently decreasing which has an impact on student learning outcomes. Therefore, to maintain concentration, students can do brain gym. The purpose of the study was to determine the effect of brain gym on the level of concentration in students at Elementary School 01 Bedalisodo, Wagir District, Malang Regency. The research design used a quasi experiment with a two-group pre-test and post-test design. The study population was 46 students in grades IV and V of SDN 01 Bedalisodo, Wagir District, Malang Regency with a sample size of 30 students (15 people in the treatment group and 15 people in the control group). Samples were taken using a simple random sampling technique. The independent variable is brain gym, the dependent variable is concentration. The instrument used a questionnaire sheet. Data analysis used a paired samples test and a Wilcoxon test for the treatment group. The results of the study in the control group showed no increase in concentration and no effect. Meanwhile, the treatment group showed an increase in concentration after being given brain gym from the high category (80.0%) to the very high category (86.7%) and the results of the statistical test showed the effect of brain gym on the level of concentration in students at Elementary School 01 Bedalisodo, Wagir District, Malang Regency with a value of p = 0.003 <0.05. Students are able to do brain gym to improve concentration. Further researchers can examine the physical health, psychology, sleep quality and room environment of students that can affect learning concentration.